Depression, Loneliness and Quality of Life in Institutionalised and Non-Institutionalised Older Adults in Portugal: A Cross-Sectional Study. - Silva, C (2024)
Our study aims to estimate the prevalence of depressive symptomatology among older adults and to assess their association with loneliness and quality of life according to institutionalisation status in a Portuguese sample. Background: The World Health Organisation estimates that by 2050, the world’s population over 60 will number two billion people, which poses complex challenges in terms of maintaining the mental health of older adults. The COVID-19 pandemic has increased the prevalence of depressive symptoms in this population, but the post-pandemic phase has not yet been studied much. Methods: A cross-sectional survey was carried out in 2023 among institutionalised and non-institutionalised older adults (total n = 525; institutionalised = 458; non-institutionalised = 67) who were selected by convenience sampling. The Patient Health Questionnaire (PHQ-9) was used to assess the presence of depressive symptoms, the WHOQOL-BREF to assess perceived quality of life and the Loneliness Scale (UCLA) to assess negative feelings of loneliness. Unconditional logistic regression models were fitted to compute crude adjusted odds ratios (ORs) and the respective 95% confidence intervals (95%CIs) for the association between sociodemographic, clinical and psychosocial characteristics and depressive symptomatology, according to institutionalisation status. The final model was adjusted for sex, age, QoL and feelings of loneliness. Results: Of the 525 participants, 74.6% of the non-institutionalised participants had no or minimal depressive symptoms, while 55.4% of the institutionalised participants fell into this category. Mild to moderately severe depressive symptoms were present in 25.4% of the non-institutionalised participants. 26.9% of the institutionalised participants had mild symptoms, 11.8% had moderate symptoms, 3.9% had moderately severe symptoms, and 2.0% had severe depressive symptoms. Overall, a higher quality of life was associated with lower levels of depressive symptoms. Participants describing feelings of loneliness were more likely also to present depressive symptoms (OR = 78.10; 95%CI 2.90–2106.08 and OR = 3.53; 95%CI 1.72–6.91 for non-institutionalised and institutionalised older adults, respectively), independently of institutionalisation status. Conclusions: The prevalence of depressive symptoms is high in older adults, which means that it has not decreased after the increase seen due to the COVID-19 pandemic. A lower perception of quality of life and the presence of negative feelings of loneliness are associated with the presence of depressive symptoms. These conclusions suggest that plans should be developed to intervene in the dimensions of depressive symptoms, perceived quality of life and negative feelings of loneliness.